Public officials' treatment of minority clients - Per Adman; Jonas Larsson Taghizadeh (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
The aim of this paper is to investigate the occurrence of discrimination based on ethnicity in public officials' treatment of welfare clients. Previous research has confirmed the existence of ethnic discrimination, but we argue that further investigations are needed. Field experiments in the form of correspondence tests, as we use here, are in many ways appropriate for discovering discrimination. However, an ethnic minority background is often perceived to be associated with low socioeconomic status (SES), which most previous field experiments have not paid attention to. Hence, ethnic discrimination may have been confused with socioeconomic discrimination. Our research design provides possibilities to take this problem into consideration. Furthermore, the research design allows investigation of whether ethnic discrimination occurs primarily among individuals with certain SES levels, which is currently an open question in the literature. Discrimination is assessed through a field experiment in which one administrator at each Swedish municipality is randomly contacted by an individual with an Arabic-sounding or a Swedish-sounding name who is interested in moving to the municipality. We find no statistically significant signs of ethnic discrimination. Admittedly, this may be due to the limited sample size and not only to our efforts of separating ethnic and socioeconomic dimensions. Furthermore, no signs of ethnic discrimination occurring at any particular SES level are discovered.
Keywords: C93; D63; D73; D91; I24; 330; ethnic discrimination; field experiment; Sweden; socioeconomic discrimination; correspondence test